TRADEMARKS AND ITS LEXICOGRAPHIC PROJECfiON IN PERUVIAN SPANISH - Calvo, Julio (2008)
In this article, a number of examples showing antonomasie is given. Through this phenomenon,and sometimes at whim, a trademark evolves to nomina te the product itself.Thus kolynos, the trade mark serves to identify the product (colinos or kolynos). The inverse movement occurs, when the libertador, for example, a general name (with minuscules)identifies a prototypic member (El libertador = Bolivar) this is also an antonomasie.